2019
DOI: 10.1002/dvdy.79
|View full text |Cite
|
Sign up to set email alerts
|

Modeling genetic epilepsies in a dish

Abstract: Human pluripotent stem cells (hPSCs), including embryonic and induced pluripotent stem cells, provide a powerful platform for mechanistic studies of disorders of neurodevelopment and neural networks. hPSC models of autism, epilepsy, and other neurological disorders are also advancing the path toward designing and testing precision therapies. The field is evolving rapidly with the addition of genome-editing approaches, expanding protocols for the two-dimensional (2D) differentiation of different neuronal subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 240 publications
(365 reference statements)
0
20
0
Order By: Relevance
“…Importantly, our results highlight the translational potential of COs to model neurodevelopmental disorders that arise from aberrant neural network formation. To date, COs have provided critical insights into the structural etiology of several neurodevelopmental disorders, including autism ( Hou et al., 2020 ; Mariani et al., 2015 ; Papariello and Newell-Litwa, 2020 ; Wang et al., 2020 ; Zhang et al., 2020 ) and epilepsy ( Niu and Parent, 2020 ; Sun et al., 2019 ). However, the characterization of neural network activity is indispensable in several of these disorders, including epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, our results highlight the translational potential of COs to model neurodevelopmental disorders that arise from aberrant neural network formation. To date, COs have provided critical insights into the structural etiology of several neurodevelopmental disorders, including autism ( Hou et al., 2020 ; Mariani et al., 2015 ; Papariello and Newell-Litwa, 2020 ; Wang et al., 2020 ; Zhang et al., 2020 ) and epilepsy ( Niu and Parent, 2020 ; Sun et al., 2019 ). However, the characterization of neural network activity is indispensable in several of these disorders, including epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous, but not heterozygous, loss of TSC1 or TSC2 disrupts the developmental suppression of mTORC1 signaling providing strong support for the two-hit hypothesis of TSC pathophysiology. They also showed that early rapamycin treatment of the brain organoids prevented development of the abnormal phenotypes ( Blair et al, 2018 ; Niu and Parent, 2019 ).…”
Section: Brain Organoids and Epilepsymentioning
confidence: 97%
“…technology (Niu & Parent, 2020). hiPSCs allow to model disease by generating neuronal cells that carry the specific genetic information of the patient and to test gene therapies in the context of the human genome, which could improve translational success (Zhao & Bhattacharyya, 2018).…”
Section: In Vitro Human Models Of Ndd + Ementioning
confidence: 99%